Mechanical Anisotropy Induced by Strain Path Change for AZ31 Mg Alloy Sheet - Chong Yang (Metals, 2020)
The variation of strain paths induces anisotropy during practical sheet forming processes, which is very important for the subsequent processing technology of anisotropic Mg alloys. In this study, two-step loading tests (tension-tension) were performed to clarify the effect of strain path changes on the evolution of anisotropy on rolled AZ31 sheet. Specimens were preloaded with tension along the rolling direction (RD) with 9% of prestrain. Then, second tension was conducted along 0°, 30°, 45°, 60° and 90° from the RD. It was found that yield strength during the second loading increased along the same direction compared to uniaxial tension without prestraining. For the second loading, the yield strength and flow stress decreased with the increase of the angle from the RD. It was found that the strain path change resulted in stronger anisotropy than that induced by texture. Moreover, it was found that the main deformation modes were basal and prismatic slips during the second loading based on visco-plastic self-consistent (VPSC) modeling. The relative activities of basal and prismatic slips were affected by the second loading direction due to texture evolution. The mechanical anisotropy induced by strain path changes was ascribed to the coupling of the heterogeneous distribution of dislocations and texture evolution induced by prestraining.